3. 已知函数$y= \tan x$,则$y''(x) =$( )。 A: $ - \sec ^ 2 x \tan x$ B: $ \sec ^ 2 x \tan x$ C: $ - 2 \sec ^ 2 x \tan x$ D: $2 \sec ^2 x \tan x$
3. 已知函数$y= \tan x$,则$y''(x) =$( )。 A: $ - \sec ^ 2 x \tan x$ B: $ \sec ^ 2 x \tan x$ C: $ - 2 \sec ^ 2 x \tan x$ D: $2 \sec ^2 x \tan x$
求函数[img=173x42]17da65390bf2806.png[/img]的导数; ( ) A: tan(pi/4 + x/2) B: (tan(pi/4 + x/2)^2/2 ) /tan(pi/4 ) C: (tan(pi/4 + x/2)^2/2 + 1/2) D: (tan(pi/4 + x/2)^2/2 + 1/2) /tan(pi/4 + x/2)
求函数[img=173x42]17da65390bf2806.png[/img]的导数; ( ) A: tan(pi/4 + x/2) B: (tan(pi/4 + x/2)^2/2 ) /tan(pi/4 ) C: (tan(pi/4 + x/2)^2/2 + 1/2) D: (tan(pi/4 + x/2)^2/2 + 1/2) /tan(pi/4 + x/2)
\( {\sec ^2}x - {\tan ^2}x = \)______. ______
\( {\sec ^2}x - {\tan ^2}x = \)______. ______
\( {\sec ^2}x - {\tan ^2}x = \)______. ______
\( {\sec ^2}x - {\tan ^2}x = \)______. ______
\(\int { { {\sec }^{3}}xdx}\)=( ) A: \(\frac{1}{2}\sec x\cot x-\frac{1}{2}\ln \left| \sec x+\tan x \right|+C\) B: \(\frac{1}{2}\sec x\tan x+\frac{1}{2}\ln \left| \sec x+\tan x \right|+C\) C: \(-\frac{1}{2}\csc x\tan x+\frac{1}{2}\ln \left| \sec x-\cot x \right|+C\) D: \(-\frac{1}{2}\sec x\tan x-\frac{1}{2}\ln \left| \csc x+\tan x \right|+C\)
\(\int { { {\sec }^{3}}xdx}\)=( ) A: \(\frac{1}{2}\sec x\cot x-\frac{1}{2}\ln \left| \sec x+\tan x \right|+C\) B: \(\frac{1}{2}\sec x\tan x+\frac{1}{2}\ln \left| \sec x+\tan x \right|+C\) C: \(-\frac{1}{2}\csc x\tan x+\frac{1}{2}\ln \left| \sec x-\cot x \right|+C\) D: \(-\frac{1}{2}\sec x\tan x-\frac{1}{2}\ln \left| \csc x+\tan x \right|+C\)
x属于(0,pi/2),tan(x)/x ×
x属于(0,pi/2),tan(x)/x ×
x属于(0,pi/2),tan(x)/x<x/sin(x)。()
x属于(0,pi/2),tan(x)/x<x/sin(x)。()
设 y=tan x, y ''=(): -2sec2x×tan x|-2secx×tan 2x.|2sec2x×tan x|2secx×tan 2x.
设 y=tan x, y ''=(): -2sec2x×tan x|-2secx×tan 2x.|2sec2x×tan x|2secx×tan 2x.
lim(1-x)tan派x/2(x趋向1)
lim(1-x)tan派x/2(x趋向1)
\( \int {\sec x(\sec x - \tan x)dx} = \)( ) A: \( \tan x - \sec x + C \) B: \( \tan x + \sec x + C \) C: \(- \tan x - \sec x + C \) D: \(- \tan x + \sec x + C \)
\( \int {\sec x(\sec x - \tan x)dx} = \)( ) A: \( \tan x - \sec x + C \) B: \( \tan x + \sec x + C \) C: \(- \tan x - \sec x + C \) D: \(- \tan x + \sec x + C \)